2017
DOI: 10.1002/pssb.201700299
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Gradient Evolution in Sputtered TiNiCuCo Films for Elastocaloric Cooling

Abstract: Elastocaloric cooling demands for temperature changes larger than 30 K to become an alternative to classical vapour compression cooling systems. The principle of active regeneration allows to exceed the materials intrinsic adiabatic temperature change. The resulting temperature gradient of the cooling demonstrator leads to a change in the thermomechanical response along the regenerator bed, according to the Clausius-Clapeyron equation. A lowered efficiency as well as an increased probability of early breakdown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The transition temperature of tailored elastocaloric films should follow the temperature gradient in the regeneration unit. In Section 3, we demonstrated that elastocaloric films can indeed be tailored by sputter deposition and a gradually changing chemical composition …”
Section: Engineering Of Sma Film‐based Cooling Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…The transition temperature of tailored elastocaloric films should follow the temperature gradient in the regeneration unit. In Section 3, we demonstrated that elastocaloric films can indeed be tailored by sputter deposition and a gradually changing chemical composition …”
Section: Engineering Of Sma Film‐based Cooling Devicesmentioning
confidence: 99%
“…Again al owered efficiency and the risk of failure would result.I nt his case samples with different transformation temperatures perpendicular to the flow direction of the cooling fluid can be used, or at ransformation gradient along the sample,w hich is placed along the flow direction of the regenerator. Both possibilities have been realized on the material site [49,50] and depictedi nF igure 6.…”
Section: Optimizing Tinicucofor Elastocaloric Cooling Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…For application in a commercial product, the ECM has to endure the reversible phase transformation process up to billions of times without failing 8,9 . Long-term stability is discussed as a major challenge for ECS [9][10][11][12][13] .…”
mentioning
confidence: 99%
“…A comparison of the long-term stability of different nickeltitanium based ECM-samples is given in Fig. 1 [8][9][10][11]13,[25][26][27][28][29][30][31][32][33] . For bulk materials, compressive loading shows a significantly better long-term stability than tensile loading 6,9,13,34,35 .…”
mentioning
confidence: 99%